Effect of Flaming Period on the Rejection Power of Plantain (Musa Sapientum L.) in Situ at Gbadolite in the Democratic Republic of Congo - Molongo Mokondande Médard; Litucha Bakokola Joseph; Okungo Lotokola Albert; Songbo Kwedugbu Médard; Monde te-Kazangba Gofroid (Budapest International Research and Critics University, 2023)
The present study was carried out to observe the effect of buckling periods on the rejection power of plantain (Musa sapientum L.) in situ at Gbadolite in the Democratic Republic of Congo. The experimental set-up chosen was that of randomized complete blocks comprising 4 blocks and 4 treatments arranged in single rows; the subjects were planted at distances of 3 m x 3 m. The treatments were as follows: T0: Untreated or non-flambé subject; T1: Flambé subject at 2 months from planting; T2: Flambé subject at 4 months and T3: Flambé subject at 6 months from planting. Each plot consisted of 10 plants. Flambéing was carried out according to the flambé period, by mowing and assembling the dry phytomasses around the test plants, and finally, incineration by running fire or moderate heat,